Elaboración de un plan de control de procesos operativos en empresas industriales - Orejuela Cabrera, César Enrique (2010)
The purpose of this project is to elaborate a control plan that will allow an efficient and scientific approach for process control and process management. The control plan will become industries more effective, productive and competitive, changing their traditional operational way to a systematic and efficient process. This project includes specific tools that support process functions in an organized and standardized manner. By having an increase in productivity, there is a significant reduction in variability and production costs. The control plan and process management are oriented to any industrial company that generate a common productive process. Its methodology and tools are obtained from the knowledge management of operational staff. The expected output is to obtain a predictable process with greater control and flow, which gives in result lower variability and client satisfaction. Another result will be to obtain a more communicative and organized workplace for all personnel.